Growing Green Minds: Understanding Primary Students’ Perspectives on Ecological Literacy - Fitriani, Somariah; Irdalisa, Irdalisa; Safi’i, Imam; Mohamad, Hamidah (International Journal of Social Learning (IJSL), 2025)
Ecological literacy is an essential aspect for fostering an understanding of and responsibility for environmental stewardship in young learners, yet limited research examines how children engage with ecological concepts in unique island-based settings. This study aimed to explore the primary pupils’ perceptions of ecological literacy at an island-based school through participation in a mangrove planting program. Employing a case study research design with ten participants, semi-structured interviews revealed five themes: foundational understanding, personal connection to nature, daily environmental awareness, environmental education value, and concern for preservation. Pupils’ attitudes toward ecological responsibility revealed seven themes: belief in personal and collective agency, practical environmental actions, environmental impact awareness, emotional connection to nature, peer encouragement participation, stewardship, and experiential learning. The results undeline the need of practical, place-based educational activities in fostering ecological literacy. This program help pupils to develop active participation and feeling of responsibility and deepen their knowledge of environmental ideas.